INTERACTIVE METHODS IN COMMUNICATIVE EDUCATION - Oksana Bulvinska; Nataliia Khanykina (Borys Grinchenko Kyiv Metropolitan University, 2019)
The article deals with the problem of using of interactive methods and forms of teaching, which are based on mutual learning, and community education. The empirical material of the research was collected by the method of questioning of academic staff from Ukrainian universities. The respondents were asked questions, grouped in 2 blocks. In the first block, the respondents had to pick up the interactive methods, which they use in teaching. The second block was a question about of the effectiveness of interactive methods. The results of the study made it possible to conclude that lecturers of Ukraine's higher education institutions use interactive methods and forms of teaching for the communicative skills and competencies development, developing communicative personality traits and accumulation of professional and communicative experience, but their choice is not diverse and there is a lack of teachers' knowledge about interactive methods and forms of teaching. These results contradict modern educational trends, which imply the activation, stimulation and encouragement of the activity of each student in the educational process.